Предмет: Алгебра, автор: Varvara2001

Упростить (2a +3x) (5a - x) – (a + x) (10a - 3x)

Ответы

Автор ответа: ZhuvikiSquirrel
0
 (2a +3x) (5a - x) – (a + x) (10a - 3x) = 10a^2-2ax+15ax-3x^2-10a^2+3ax-10ax+3x^2=6ax
Автор ответа: Аноним
0
(2a +3x) (5a - x) – (a + x) (10a - 3x) = 10a^2-2ax+15ax-3x^2-10a^2+3ax-10ax+3x^2=6ax
Автор ответа: Аноним
0
правильно
Автор ответа: Murрhу
0
(2a+3x)(5a-x)-(a+x)(10a-3x)= \ =10a^2-2ax+15ax-3x^2-(10a^2-3ax+10ax-3x^2)= \ =10a^2+13ax-3x^2-10a^2-7ax+3x^2=6ax.
Похожие вопросы